Effects of the multi‐kinase inhibitor midostaurin in combination with chemotherapy in models of acute myeloid leukaemia. Issue 5 (22nd January 2020) - Weisberg, Ellen; Meng, Chengcheng; Case, Abigail E.; Tiv, Hong L.; Gokhale, Prafulla C.; Buhrlage, Sara J.; Yang, Jing; Liu, Xiaoxi; Wang, Jinhua; Gray, Nathanael; Adamia, Sophia; Sattler, Martin; et al.
Abstract: Recently, several targeted agents have been developed for specific subsets of patients with acute myeloid leukaemia (AML), including midostaurin, the first FDA‐approved FLT3 inhibitor for newly diagnosed patients with FLT3 mutations. However, in the initial Phase I/II clinical trials, some patients without FLT3 mutations had transient responses to midostaurin, suggesting that this multi‐targeted kinase inhibitor might benefit AML patients more broadly. Here, we demonstrate submicromolar efficacy of midostaurin in vitro and efficacy in vivo against wild‐type (wt) FLT3‐expressing AML cell lines and primary cells, and we compare its effectiveness with that of other FLT3 inhibitors currently in clinical trials. Midostaurin was found to synergize with standard chemotherapeutic drugs and some targeted agents against AML cells without mutations in FLT3. The mechanism may involve, in part, the unique kinase profile of midostaurin that includes proteins implicated in AML transformation, such as SYK or KIT, or inhibition of ERK pathway or proviability signalling. Our findings support further investigation of midostaurin as a chemosensitizing agent in AML patients without FLT3 mutations.